2022
DOI: 10.1177/2164957x221126484
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Interprofessional Collaboration and Referral to Mindfulness-Based Stress Reduction Programs

Abstract: Background In 2017, the American College of Physicians (ACP) designated Mindfulness-Based Stress Reduction (MBSR), an eight-week group program, as first-line non-pharmacological treatment for chronic low back pain. However, interprofessional collaboration between mindfulness instructors and Primary Care Providers (PCP) remains largely unknown. Objective We developed a survey to assess communication between mindfulness instructors and PCPs, identify predictors of referral to MBSR, and determine areas where inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
(60 reference statements)
0
0
0
Order By: Relevance
“…20 Patients with chronic pain, chronic illness, or a stress-related problem and without uncontrolled psychiatric illnesses found that an eight-week MBSR program led to significant improvements in self-reported pain, psychological symptoms, and reduced health services utilization. 21…”
Section: Types Of Interventionmentioning
confidence: 99%
“…20 Patients with chronic pain, chronic illness, or a stress-related problem and without uncontrolled psychiatric illnesses found that an eight-week MBSR program led to significant improvements in self-reported pain, psychological symptoms, and reduced health services utilization. 21…”
Section: Types Of Interventionmentioning
confidence: 99%